The Edukasi Kehalalan pada Produk Pangan untuk Anggota Aisyiyah Jatimakmur - Azharita, Ristianti; Rahmi, Hanifah; Yuniarti, Fitri (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Halal food products are an important thing to be understood by all Muslims. Seeing Indonesia is the country with the largest number of Muslims in the world. Most Indonesian people, especially Muslims, lack or do not understand about halal or haram in food products. This activity aims to provide knowledge to partners about the importance of eating halal food and avoiding food that is syubhat and haram. Method: The team consists of lecturers and students of the Faculty of Pharmacy and Science UHAMKA. Activities will be reviewed on Monday-Tuesday, February 27-28, 2023. Our partner in the Community Partnership Program (PKM) was Branch Leader Aisyiyah Jatimakmur, attended by 21 participants. We use methods: pretest, material delivery, dialogue accompanied by question and answer and posttest. Results: Participants understand the types of food that are halal, haram, and syubhat Conclusion: There is an increase in understanding of halal food products after the presentation of material on halal food. With this activity, it is hoped that Aisyiyah cadres will have a better understanding of halal food products and can provide this information to the community. The participants looked excited when the speaker presented the materials explained and also gave a very good response when asking questions.